The Dawn of Plant Molecular Biology: How Three Key Methodologies Paved the Way. Issue 4 (20th April 2022) - Somssich, Marc
Abstract: The adoption of Arabidopsis thaliana in the 1980s as a universal plant model finally enabled researchers to adopt and take full advantage of the molecular biology tools and methods developed in the bacterial and animal fields since the early 1970s. It further brought the plant sciences up to speed with other research fields, which had been employing widely accepted model organisms for decades. In parallel with this major development, the concurrent establishment of the plant transformation methodology and the description of the cauliflower mosaic virus (CaMV) 35S promoter enabled scientists to create robust transgenic plant lines for the first time, thereby providing a valuable tool for studying gene function. The ability to create transgenic plants launched the plant biotechnology sector, with Monsanto and Plant Genetic Systems developing the first herbicide‐ and pest‐tolerant plants, initiating a revolution in the agricultural industry. Here I review the major developments over a less than 10‐year span and demonstrate how they complemented each other to trigger a revolution in plant molecular biology and launch an era of unprecedented progress for the whole plant field. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. [Correction added on May 16, 2022, after first online publication: CAUL funding statement has been added.]